Interactive Model of Executive Functions to Understand Error Correction - Carlos Ramos-Galarza; Jorge Cruz-Cárdenas; Valentina Ramos (Ital Publication, 2022)
This article reports an investigation aimed at analyzing an interactive model of executive functions, which seeks to explain the process followed by human beings to correct their mistakes. The method followed was an analysis based on structural equations, considering the maximum likelihood process around a model that considered six executive functions. We worked with a randomized sample of 771 subjects (mean age = 39.86, SD = 15.47; 50.5%, women, 50.50%). The findings suggest that error correction is a complex executive function as it is the product of the internal language capacity that regulates behavior and cognition, adequate regulation of the limbic system, adequate decision-making, and control of automatic impulses, determining how to act and verify the thoughts and behavior of the subject. The contribution of the proposed theoretical model lies in understanding the process by which human beings manage to correct errors. In addition, how this explanatory model could help neuropsychological intervention processes to work on this cognitive ability in individuals with difficulties in correcting errors. Doi: 10.28991/ESJ-2022-06-02-011 Full Text: PDF